Acute disseminated encephalomyelitis: Updates on an inflammatory CNS syndrome. (30th August 2016) - Pohl, Daniela; Alper, Gulay; Van Haren, Keith; Kornberg, Andrew J.; Lucchinetti, Claudia F.; Tenembaum, Silvia; Belman, Anita L.
Abstract : Acute disseminated encephalomyelitis (ADEM) is an immune-mediated demyelinating CNS disorder with predilection to early childhood. ADEM is generally considered a monophasic disease. However, recurrent ADEM has been described and defined as multiphasic disseminated encephalomyelitis. ADEM often occurs postinfectiously, although a causal relationship has never been established. ADEM and multiple sclerosis are currently viewed as distinct entities, generally distinguishable even at disease onset. However, pathologic studies have demonstrated transitional cases of yet unclear significance. ADEM is clinically defined by acute polyfocal neurologic deficits including encephalopathy. MRI typically demonstrates reversible, ill-defined white matter lesions of the brain and often also the spinal cord, along with frequent involvement of thalami and basal ganglia. CSF analysis may reveal a mild pleocytosis and elevated protein, but is generally negative for intrathecal oligoclonal immunoglobulin G synthesis. In the absence of a specific diagnostic test, ADEM is considered a diagnosis of exclusion, and ADEM mimics, especially those requiring a different treatment approach, have to be carefully ruled out. The role of biomarkers, including autoantibodies like anti–myelin oligodendrocyte glycoprotein, in the pathogenesis and diagnosis of ADEM is currently under debate. Based on the presumed autoimmune etiology of ADEM, the current treatment approach consists of early immunotherapy. Outcome of ADEM in pediatric patients is generally favorable, but cognitive deficits have been reported even in the absence of other neurologic sequelae. This review summarizes the current knowledge on epidemiology, pathology, clinical presentation, neuroimaging features, CSF findings, differential diagnosis, therapy, and outcome, with a focus on recent advances and controversies.